RULES AND METHOD OF SUPPORTING THE DECISION MAKING ABOUT THE POSSIBILITY OF DONATION AND TRANSPLANTATION BASED ON THE CIVIL LAW - HNATCHUK, Yelyzaveta (Herald of Khmelnytskyi National University. Technical sciences, 2022)
Today in Ukraine the problem of transplantation of organs and other anatomical materials to humans is very acute. Every year, thousands of Ukrainians need organ transplants to save their lives, but there are only a few transplant surgeries. In developed countries, organ transplantation is the standard of care for many diseases of the kidneys, heart, liver, lungs and others. Among the reasons hindering the development of transplantation of anatomical materials to humans in Ukraine is the unpreparedness of the Unified State Information System for Organ and Tissue Transplantation (USIST). According to the author, the functioning of USIST will not be complete without a successfully developed and implemented module of supporting the decision making about the possibility of donation and transplantation based on the civil law, which will help decide on the possibility or impossibility of donation and transplantation in a given case considering civil law grounds. Developed methods of supporting the decision making about the possibility of donation and transplantation based on the civil law make it impossible to make incorrect (illegal) decisions on the possibility/impossibility of donation and/or transplantation. The use of the developed methods increases the level of correctness of the decisions made regarding donation and transplantation. Thus, the module of supporting the decision making about the possibility of donation and transplantation based on the civil law of the USIST will allow: rapid and automatic verification of all civil legal grounds for inclusion in the Register of Donors or the List of persons for transplantation, respectively; making unmistakable (from the point of view of civil law) decisions on donation and transplantation; minimizing the influence of subjectivity and the human factor in making decisions about the possibility/impossibility of donation and transplantation. Therefore, an important and urgent task now is the implementation of the designed module of supporting the decision making about the possibility of donation and transplantation based on the civil law.